Association of pvc genes expression with Biofilm formation in Clinical Isolates of Pseudomonas aeruginosa - Noor Ali; Shatha Thanoon Ahmed; Asmaa M. Salih Almohaidi (مجلة بغداد للعلوم)
PvcABCD are cluster of genes found in Pseudomonas aeruginosa. The research was designed to examine the relationship between the pvc genes expression and cupB gene, which plays a crucial role in the development of biofilm, and rhlR, which regulates the expression of biofilm-related genes, and to investigate whether the pvc genes form one or two operons. The aims were achieved by employing qRT-PCR technique to measure the gene expression of genes of interest. It was found that out of 25 clinical isolates, 21 isolates were qualified as P.aeruginosa. Amongst, 18(85.7%) were evaluated as biofilm producers, 10 (47.6%), 5 (23.8%), and 3 (14.2%) were evaluated as strong, moderate and weak producers respectively, while, 3 (14.2%) were considered as a non-biofilm forming isolate. The pvcA and pvcB were shown to be over-expressed (>2) fold in all biofilm-producer isolates, similar to that observed in cupB and rhlR, while pvcC and pvcD showed to be down-regulated (<0.5) fold in these isolates. These findings imply that the pvc genes are organized into two operons, pvcAB, and pvcCD, and genes involved in biofilm formation are regulated by pvcAB operon. This is the first study in Iraq to investigate these genes.